Inclusão de tanino na ração para equinos contra ciatostomíneos - GLENDA LAYSA DE SOUSA E SILVA (2023)
This review was carried out with the aim of presenting a description of tannins and their characteristics, covering the main aspects related to their use as an antiparasitic agent, understanding how gastrointestinal parasitism can affect horses and which auxiliary methods exist for the available drugs. Cyathostomines are the most prevalent helminths for horses, mainly in animals considered clinically healthy and that have undergone deworming protocols against other types of helminths. The indiscriminate use of anthelmintic drugs has led to the emergence of resistance and ineffectiveness of commercial molecules. As an auxiliary measure to the classes of vermifuge released for use in horses, tannin has been greatly studied due to its use in ruminants, mainly sheep. It is a compound of the secondary metabolism of plants with biological activity, such as the anthelmintic effect, which can be justified by some factors, the main ones being its ability to complex with dietary protein, preventing degradation in the rumen and, consequently, improving the supply of amino acids and immune response or even performing this same connection with parts of the parasite, rich in protein, causing cuticular alterations that would make its survival unfeasible. Only two modes of action have been proposed as an effect of tannins on the host and on the parasite, but so far these processes have not been fully elucidated and it is not known how tannin can improve the host's direct resilience to non-ruminant animals, such as the horses. Therefore, tannin is a promising auxiliary method for commercial deworming agents, which have already shown less and less effectiveness.